Bloom of Trichogloeopsis pedicellata (Rhodophyta, Nemaliales) following hurricane Iota in San Andrés, Southwestern Caribbean Sea - Gavio, Brigitte; Prato, Julián; Gnecco, Mariana; Maya, María Fernanda; Mancera-Pineda, José Ernesto (Frontiers in Marine Science, 2022)
Hurricanes and tropical storms are major climatic disturbances with potentially catastrophic effects on coastal and marine ecosystems. The impact of these climatic events on coastal communities may vary greatly and depends on the hurricane’s severity, trajectory, and duration. Furthermore, the impact of hurricanes can be patchy, causing extensive damage in some locations, while leaving other subjacent areas intact. In coral reef areas, breakage, dislodgement, and sandblasting may cause extensive coral mortality, and loss of coral cover may increase due to sedimentation and freshwater runoff. After the impact of the climatic event, successional stages in the reef community have been observed, where blooms of ephemeral algae may occupy space made available by the storm impact. We report a bloom of the red alga Trichogloeopsis pedicellata on the west coast of the island of San Andrés, following Hurricane Iota. The survey was carried out in seven locations at different depths: shallow (2–5 m) and deep (8–15 m). Three video transects were recorded at each sampling site, and 15 photo quadrats were analyzed for benthic cover. For the biomass estimate, three to five quadrats of 25 × 25 cm were laid on the substrate, all the algae inside were collected, and their wet biomass was determined. The algal cover reached 100% in some locations, with wet biomass up to 5,264 g/m2, and persisted for several weeks. The bloom was more severe at shallow depths. Apparently, the availability of the substrate due to the detachment of foliose algae triggered the bloom. After a few months, the bloom receded naturally.